Are teachers literate in formative assessment? The development and validation of the Teacher Formative Assessment Literacy Scale. (September 2022) - Yan, Zi; Pastore, Serafina
Abstract: Despite the critical role of formative assessment in instruction, there is a lack of theory-driven instruments that specifically assess teachers' formative assessment literacy. This paper reports the development and validation of the Teacher Formative Assessment Literacy Scale (TFALS). The instrument was developed on a three-dimensional model of formative assessment, aiming at assessing the conceptual, practical, and socio-emotional aspects of formative assessment literacy. Survey data were collected from 585 teachers in Hong Kong primary and secondary schools. Exploratory factor analysis suggests a three-factor structure, and confirmatory factor analysis supports this structure. Rasch analysis results further support its scale dimensionality and item quality. In addition, the relations between TFALS scores and teachers' formative assessment practices demonstrate the instrument's external validity. Overall, the results suggest that the TFALS is an appropriate instrument for assessing teachers' formative assessment literacy. The potential of using the TFALS in research and practice is discussed. Highlights: The TFALS assesses teachers' formative assessment literacy. The TFALS contains conceptual, practical, and socio-emotional dimensions. The scale quality was examined and endorsed by factor analysis and Rasch analysis.